2012
DOI: 10.1007/s10342-012-0661-2
|View full text |Cite
|
Sign up to set email alerts
|

What role for photoperiod in the bud burst phenology of European beech

Abstract: A considerable number of studies have investigated the phenology of European beech using models, experimental controlled conditions, or descriptive surveys of patterns in situ. In spite of this interest, there is no consensus about the environmental factors controlling bud burst in beech, especially about the role of photoperiod and chilling temperature (cold temperature effective to release bud dormancy). However, recent experimental and modelling studies provide new insights into the means by which these env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
155
4
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 186 publications
(172 citation statements)
references
References 45 publications
10
155
4
3
Order By: Relevance
“…Once the chilling requirement is fulfilled, trees enter the ecodormancy phase and flush when a certain amount of warmth has accumulated. Chilling has been found to be important for oak and beech trees (20,23,24), our two study species, with beech having a particularly high chilling requirement (34). In this study, the earlier leaf senescence observed in the warm treatments applied during previous winter/ early spring (Table 1 and Fig.…”
Section: Discussionmentioning
confidence: 52%
“…Once the chilling requirement is fulfilled, trees enter the ecodormancy phase and flush when a certain amount of warmth has accumulated. Chilling has been found to be important for oak and beech trees (20,23,24), our two study species, with beech having a particularly high chilling requirement (34). In this study, the earlier leaf senescence observed in the warm treatments applied during previous winter/ early spring (Table 1 and Fig.…”
Section: Discussionmentioning
confidence: 52%
“…The influence of warm spring temperatures is particularly obvious in mountainous areas, where tree populations flush gradually later toward higher elevations (Vitasse et al 2009), with only a small fraction of the variability explained by the genetic differentiation among populations . Finally, several studies have suggested that the influence of a warm temperature in early spring depends on the state of bud endodormancy and, in certain species (such as Fagus sylvatica or Picea abies), on the current photoperiod (Heide 1993;Myking and Heide 1995;Caffarra et al 2011b;Vitasse and Basler 2013;Basler and Körner 2014;Laube et al 2014). However, the effect of the photoperiod on the resumption of bud cell division and growth during ecodormancy varies widely among species and has been reported to clearly affect the timing of budburst in only one third of the temperate and boreal tree species for which this factor has been explicitly tested in experiments (18 out of 55 tree species, mainly temperate trees; Way and Montgomery 2014).…”
Section: Phenology Of Leaves and Reproductive Structuresmentioning
confidence: 99%
“…Temperatures at different times of the year can have opposing effects, with the forcing effect of warm springs usually advancing phenology, while warm conditions in autumn/winter may delay phenology via effects on dormancy induction, breaking dormancy and stimulating growth (Murray et al, 1989;Polgar & Primack, 2011;Laube et al, 2014;Roberts et al, 2015). Experimental studies reveal that photoperiod plays a key role in some species (Caffarra & Donnelly, 2011), although the precise nature of any interactions between photoperiod and the response to forcing and/or chilling temperatures is not known for most species (Polgar & Primack, 2011;Vitasse & Basler, 2013). While longitudinal data from a single site are not informative about the role that photoperiod plays, spatial replication of longitudinal data across latitudes may be (Phillimore et al, 2013), and such data are often collected by citizen science schemes.…”
Section: Introductionmentioning
confidence: 99%